MarkSim DSSAT weather file generator - CGIAR Research Program on Climate Change, Agriculture and Food Security; International Livestock Research Institute; International Center for Tropical Agriculture (2014)
MarkSim is a tool that generates simulated daily weather data specifically designed for use in the tropics, including rainfall, maximum and minimum temperatures and solar radiation. It provides files of daily weather data.